# Stuck while deriving the Lindblad Master Equation

I was following Quantum Markov Processes from the book The Theory of Open Quantum Systems by Breuer and Petruccione. In the section The Markovian Quantum Master Equation they proceeds to 'construct the most general form for the generator $$\mathcal{L}$$ of a quantum dynamical semigroup.' Then I observed that almost the same approach is taken in the book Quantum Dynamical Semigroups and Applications by Alicki and Lendi, so I moved there.
We have the definition of $$\mathcal{L}$$: $$\frac{d}{dt}\rho_t=\mathcal{L}\rho_t$$ with $$\rho_t=\Lambda_t\rho$$. And this gives $$\Lambda_t=e^{\mathcal{L}t}, t\ge0.$$
For unbounded $$\mathcal{L}$$ they have used the following definition of exponential - $$e^{\mathcal{L}t}\rho=\lim\limits_{n \to \infty}\left(1-\frac{t}{n}\mathcal{L}\right)^{-n}\rho.$$ After that,

We find now a general form of $$\mathcal{L}$$ in the case of finite-dimensional Hilbert space $$\mathcal{H_S}$$ (dim $$\mathcal{H_S} = N$$). Introducing a linear basis {$$F_k$$}, $$k =$$ $$0,1,... ,N^2 − 1$$ in $$\mathcal{B(H_S)}$$ such that $$F_0 = \mathbb{1}$$ we may write a time-dependent version of $$\Lambda\rho=\sum_{\alpha} W_{\alpha}\rho W_{\alpha}^*$$ as follows, $$\Lambda_t\rho=\sum_{k,l=0}^{N^2-1}C_{kl}(t)F_k\rho F_l^*,$$ where $$C_{kl}(t)$$ is a positive-definite matrix.

The part after this is what I'm totally in the dark with. Let me paste the photo as it will be too much effort to type:

How are we getting this expression for $$\mathcal{L}\rho$$ with all these limits, $$\epsilon$$'s and all that? What I got is the following: $$\mathcal{L}\rho=\frac{d}{dt}\rho_t=\frac{d}{dt}{[\Lambda_t\rho]}=\frac{d}{dt}\left(\sum_{k,l=0}^{N^2-1}C_{kl}(t)F_k\rho F_l^*\right)$$ but can proceed no further.

You have to be careful with the notation, $$\rho = \rho_0$$ is the initial state here. The left hand side of your last equation should be $$\mathcal L \rho_t$$.
We thus have to evaluate the equation at $$t=0$$, obtaining $$\mathcal L \rho = \frac{d}{dt} \Bigl( \sum_{kl} C_{kl}(t) F_k \rho F_l^\dagger \Bigr)_{t=0} .$$
The result now follows from $$\left. \frac{d}{dt} f(t) \right|_{t=0} = \lim_{\epsilon \to 0} \frac{1}{\epsilon} \bigl( f(\epsilon) - f(0) \bigr) ,$$ that is, $$\mathcal L \rho = \lim_{\epsilon \to 0} \frac{1}{\epsilon} \bigl( \Lambda_\epsilon \rho - \rho \bigr)$$.
There is a typo in Alicki / Lendi, the sums in the final result are all supposed to start at $$1$$ instead of zero. The same calculation can be found for example in the proof of Thm. 5.1 in the Rivas / Huelga book, I think it is a bit easier to understand there.
• Sorry for the late reply. Thanks, it makes sense @Noiralef. Also, regarding your edit, I think you are talking about a typo in the original Alicki & Lendi book, right? While proceeding to the final form, I also had to make two guesses, of course without being able to prove: 1. $C_{kl}(t)|_{t=0}=\mathbb{1}$; 2. $C_{kl}(t)|_{t=0}=0$, unless $k$ and $l$ are simultaneously zero. Any comment on this will be highly valued. Thanks! Commented Sep 28, 2023 at 19:02
• @QuestionTheAnswer These guesses should be correct, but you don't even need that. The $t=0$ terms are $\Lambda_0 \rho$ which is equal to $\rho$ by definition. I have edited my answer a bit more. Commented Sep 29, 2023 at 0:35